Relationship between bone mineral density and radiologic scores of hands in rheumatoid arthritis - Ardicoglu, O; Ozgocmen, S; Kamanli, A; Pekkutucu, I (Elsevier Science Inc, 2001)
This study proposed to assess the relationship between hand bone mineral density (BMD) and radiographic scoring methods, important measures to assess the course of rheumatoid arthritis. Hand, spine, and femur BMD of 49 patients with rheumatoid arthritis and 34 age- and sex-matched healthy control subjects were measured using dual X-ray absorptiometry and the results were compared. Standard hand films of patients were scored according to five different scoring methods-Larsen method, modified Larsen method, Sharp/van der Heijde modified method, carpo:metacarpal ratio, and simple erosion narrowing score (SENS)-and were correlated with hand BMD. There was a moderate relationship between hand BMD measurements and radiologic scores. SENS was the method that correlated significantly with the highest correlation coefficient. Hand BMD correlated significantly with disease duration and c-reactive protein levels. Hand BMD in patients with rheumatoid arthritis was significantly lower than in control subjects, whereas there was no significant difference in axial BMD measurements. The advantages and disadvantages of hand BMD and radiographic scoring methods were determined. Our results indicate that hand BMD measurements may be as useful is assessing, the course of rheumatoid arthritis as radiologic scoring methods. However to prove this, a well-designed reference population for hand BMD and longitudinal studies are required.
Keywords: rheumatoid arthritis; hand bone mineral density; radiologic scoring